Hyperattenuating lesions after mechanical thrombectomy in acute ischaemic stroke: factors predicting symptomatic haemorrhage and clinical outcomes. Issue 1 (January 2021) - Bae, S.; Ahn, S.S.; Kim, B.M.; Kim, D.J.; Kim, Y.D.; Nam, H.S.; Heo, J.H.; Lee, S.-K.
Abstract : AIM: To evaluate the clinical significance of hyperattenuating lesions on CT after mechanical thrombectomy for acute ischaemic stroke, and to identify imaging factors that predict symptomatic haemorrhage and unfavourable outcomes. MATERIALS AND METHODS: Seventy-eight patients with acute ischaemic stroke in the anterior circulation who underwent mechanical thrombectomy were evaluated. All patients underwent post-interventional unenhanced computed tomography (CT) within 24 h and follow-up CT or magnetic resonance imaging (MRI) within 7 days. Baseline characteristics and clinical outcomes were compared between patients with and without hyperattenuating lesions. In patients with hyperattenuating lesions, clinical and imaging factors that predict symptomatic haemorrhage and unfavourable outcomes were determined. RESULTS: Fifty-six of 78 patients (71.8%) demonstrated hyperattenuating lesions on post-interventional CT. Patients with hyperattenuating lesions showed lower Alberta Stroke Program Early CT score (ASPECTS), persistent/symptomatic haemorrhage, and unfavourable outcomes than those without. In patients with hyperattenuating lesions, larger hyperattenuating lesion volume (>21.3 ml; OR, 55.60, p< 0.001) and perilesional oedema (OR, 46.04, p= 0.015) were independent factors predicting symptomatic haemorrhage. Older age (OR, 1.2, p= 0.006) and lower ASPECTS (OR, 0.45, p= 0.046) were independent factors predicting unfavourable outcomes in patients with hyperattenuating lesions. Adding the volume of the hyperattenuating lesion to age and ASPECTS increased the predictive performance of unfavourable outcomes (area under the curve 0.874 versus 0.934, p= 0.043). CONCLUSIONS: Hyperattenuating lesions on post-interventional CT are associated with increased risk of symptomatic haemorrhage and unfavourable outcomes. Larger hyperattenuating lesion volume is an independent factor of symptomatic haemorrhage and it has added predictive value for unfavourable outcomes. Highlights: Hyperattenuating lesion after thrombectomy is associated with symptomatic hemorrhage. Hyperattenuating lesion after thrombectomy is associated with unfavorable outcomes. Larger hyperattenuating lesion volume has predictive value for symptomatic hemorrhage. Larger hyperattenuating lesion volume has predictive value for unfavorable outcomes.